Identification of spatial interactions associated with the worship to Cristo Mojado (Wetback Christ) in the Saint Cecilia Catholic Church in Los Angeles, California, United States - Rosas-Paz, Leonardo Daniel; Propin-Frejomil, Enrique (Revista Geográfica de América Central., 2021)
The Cristo Mojado (Wetback Christ) is a replica of the Lord of Esquipulas, Guatemala, taken to Los Angeles, California, in an undocumented way by devout migrants of Central American origin in 2003. As of his arrival, devotion to the image expanded and Spatial relationships began to be articulated at different geographic-scalar levels, the anchoring of which is sustained by the diverse social practices of the migrant community that meets in the Church of Santa Cecilia. In this context, this work reveals various spatial interactions associated with the devotion to the Wet Christ of the Church of Santa Cecilia in Los Angeles. For this, cognitive positions associated with the theory of spatial interaction are exposed, the methodological strategy followed in place during the 2018 patronal festival is specified and the investigative findings associated with the arrival of the image to the church of Santa Cecilia and the spatial importance of its cult.